Protein bank as a feeding complement to heifers reared in native Cerrado pasture - Zoby, José Luiz Fernandes; Kornelius, Euclides; Saueressig, Moacir Gabriel (Pesquisa Agropecuaria Brasileira, 2014)
The low quality of the diet for beef cattle has been the major problem in the Cerrado region. Females reared on Cerrado native pastures start the reproductive phase very late. A protein bank as a complement to native pasture was evaluated by raising females in order to antecipate first mating. Two experiments were carried out with Leucaena leucocephala cv. Cunningham and Stylosanthes guianensis “tardio” group established in upland rice. The protein bank was grazed rotationaly. Females remained in the experimental area from 9 to 27 months of age. It was concluded that leucaena should be used during the rainy season and stylo in the dry season to avoid weight losses. Twenty seven-month old females with access to protein banks weighed 65 to 95 kg more than the animals grazing only native pasture.